Tanggungjawab Perseroan atas Tindakan Direksi yang Melebihi Kewenangannya (Analisa Terhadap Doktrin Ultra Vires) - Akbar Hidayatullah Vidi Hartono; Muhammad Didin (Lembaga Pengembangan Kinerja Dosen, 2023)
The Company is currently included in the qualification of a separate legal subject where to run the wheels of the company there must be an organ that runs it consisting of the General Meeting of Shareholders (GMS), the Board of Directors, and also the Board of Commissioners. The Board of Directors itself is an organ that carries out operations in a Company so that what is done by the Board of Directors is considered an act committed by the Company, but in this case there is no limit on when the directors are responsible for what they do when there is a violation and when the Company is responsible for what the directors do for the benefit of the Company When there is a violation. This research is a type of normative research which is not only descriptive It only explains what is true, and what is false of each problem and what factors influence. while the approach carried out in this study is the Law Approach Research (Statute approach) and case approach (case approach). And also The source of legal material in this study consists of primary legal material and secondary legal material. While the method of analysis of legal materials in this study is descriptive analytical which aims to describe precisely a problem.